Isolation of the superior vena cava from the right atrial posterior wall: a novel ablation approach. Issue 9 (15th September 2017) - Gianni, Carola; Sanchez, Javier E; Mohanty, Sanghamitra; Trivedi, Chintan; Della Rocca, Domenico G; Al-Ahmad, Amin; Burkhardt, J David; Gallinghouse, G Joseph; Hranitzky, Patrick M; Horton, Rodney P; Di Biase, Luigi; Natale, Andrea
Abstract: Aims: Superior vena cava (SVC) isolation might be difficult to achieve because of the vicinity of the phrenic nerve (PN) and sinus node. Based on its embryogenesis, we hypothesized the presence of preferential conduction from the right atrial (RA) posterior wall, making it possible to isolate the SVC antrally, sparing its anterior and lateral aspect. Methods and results: This is a descriptive cohort study of 105 consecutive patients in which SVC isolation was obtained with radiofrequency ablation, starting in the septal aspect of the SVC–RA junction and continued posteriorly and inferiorly targeting sites of early activation until electrical isolation was obtained. Acute SVC isolation was achieved in 103 (98%) patients; the mean distance between the site of SVC isolation and the SVC–RA junction was 19.9 ± 5.3 (range 9.7–33.7) mm. During follow-up, 2 (2%) patients developed symptomatic diaphragmatic paralysis due to transient right PN injury; 13 patients underwent a repeat ablation: SVC reconnection was observed in 5 patients, and re-isolation was easily achieved by targeting the corresponding sites of early activation. Conclusion : Superior vena cava isolation can be completed by targeting its septal segment and sites of early activation in the posterior SVC–RA junction and RA posterior wall; this is a feasible alternative ablation strategy in patients in which SVC isolation cannot be completed with the standard approach. The risk of sinus node injury or SVC stenosis are eliminated; PN injury is still possible but can easily be prevented with high-output pacing to exclude a true posterior course of the PN.